Myaka : Aplikasi Pengelolaan Arsip Digital Sekolah - Fachzriati, Mai Sella; Lolytasari, Lolytasari; Waruwu, Nurdelima (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
This study aims to describe filing management using the Myaka application. The method used in this study is to use a qualitative approach with descriptive methods. Data was collected through interviews, observation, and documentation studies. The results of this study indicate that the development of information and communication technology (ICT) has now spread to the world of education, namely with the management of digital archives. The Myaka application is school software as digital archive data used by schools to manage grades, attendance, report cards, question analysis, student data, and teacher data collected in one system. This study found that Myaka, as a digital archive storage application, has fulfilled the requirements in the archive life cycle starting from the creation, storage, distribution, user, maintenance, and disposition.